(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
A synthesis of almost two decades of archaeological excavations in Nora (CA) allows us to reconsider some historical and urbanism aspects of the ancient city. The research focused on the central area, already partially investigated during the 50s and the 60s: new data emerged relating above all to private buildings, their stratigraphic and planimetric articulations, and their decorative elements, including mosaics and frescoed walls.